TEMPORAL HEAVY METALS VARIATION IN VEGETABLES SAMPLED AT KASUWAN MATA, KADUNA METROPOLIS, NIGERIA. - A.Y, Ugya; T.S, Imam (Malaysian Journal of Science, 2017)
The study is aimed at assessing monthly heavy metals variation in some selected vegetables sampled from Kasuwan Mata, Igabi Local Government Kaduna. Vegetables samples were collected and analysed for Pb, Cu, Zn, Ni, Mn Cr and Cd using Atomic Absorption Spectrophotometric techniques for the period of 4 month. Results show high heavy metal concentration in the month of november when compared to the month of august, September and October, all the heavy metal concentration in the vegetables were within WHO/FAO permissible limits but these can cause hazardous health effects in people, who are ingesting these vegetables for long period of time due to magnification of these heavy metals in their body. It is thereby recommended that KEPA should serve as references laboratory for the approval of farmers that intend to undertake dry farming. Keywords: AAS, Heavy Metals, Water Pollution, Irrigration, Seasonal Variation